Modified risk stratification based on cervical lymph node metastases following lobectomy for papillary thyroid carcinoma. (12th November 2019) - Song, Eyun; Ahn, Jonghwa; Song, Dong Eun; Kim, Won Woong; Jeon, Min Ji; Sung, Tae‐Yon; Kim, Tae Yong; Chung, Ki Wook; Kim, Won Bae; Shong, Young Kee; Hong, Suck Joon; Lee, Yu‐Mi; et al.
Abstract: Objective: Evidence for American Thyroid Association (ATA) risk stratification stems largely from studies involving patients undergoing total thyroidectomy. We aimed to assess the risk of recurrence according to the present ATA risk stratification system in patients who underwent lobectomy. Design: Retrospective cohort study. Patients: Patients who underwent thyroid lobectomy for 1‐4 cm‐sized papillary thyroid carcinoma (n = 571). Measurements: Disease‐free survival (DFS) was compared according to the ATA risk stratification, and specific lymph node (LN) characteristics were evaluated to modify the ATA criteria with a higher predictability for recurrence. Results: Based on the ATA risk stratification, 439 patients (61.1%) were classified into intermediate‐ or high‐risk group, and consideration for completion thyroidectomy is suggested by ATA guidelines for these patients. However, no significant differences were found in DFS among the low‐, intermediate‐ and high‐risk groups ( P  = .9). In contrast, when patients were stratified according solely to the LN criteria from the ATA risk stratification, only 127 patients (22.2%) had intermediate risk (intermediate‐N1a) and exhibited significantly poorer DFS than those with N0 disease ( P  = .035). Modifying the intermediate‐N1a criteria by adding the extranodal extension (ENE) status and omitting the clinical nodal disease enabled the subclassification of 19 patients (3%) with a high risk for recurrence. Conclusions: The present study suggests that risk stratification based solely on LN metastases is more reasonable for predicting structural persistence/recurrence following lobectomy than that based on the overall ATA criteria. Considering the ENE status can assist in selecting patients with a high risk of recurrence to minimize further treatments.